Advanced Anal Carcinoma during Pregnancy: A Case Report - García Prado, Diego; Arche Prats, Jorge; Readi Vallejos, Alejandro; Campaña Villegas, Gonzalo (Journal of Coloproctology, 2024)
Objective To present a rare case of anal squamous cell carcinoma (SCC) in a young pregnant woman.Material and Methods The information was collected based on the clinical record after obtaining the informed consent of the patient.Results This is the case of a 34-year-old pregnant woman with stage IIIB anal SCC. She was treated with chemotherapy before delivery, followed by cesarean section and chemoradiotherapy after birth. The patient experienced complete clinical and imaging regression after treatment, but she presented early tumor regrowth requiring abdominoperineal amputation, with negative surgical margins.Discussion The treatment of anal cancer in pregnant women is based on a multidisciplinary approach, adapting current clinical guidelines. It establishes a challenge from an ethical point of view that must consider the impact on the health of the mother and the fetus. Anal screening in carriers of cervical pathology due to papilloma virus would be a good tool for early detection.
Keywords: anal cancer; pregnancy; squamous cell carcinoma; cervical dysplasia; papillomavirus infection